Schwann-like cells seeded in acellular nerve grafts improve nerve regeneration - Fan, Lihong (BioMed Central, 2014)
BACKGROUND: This study evaluated whether Schwann-like cells (SLCs) induced from bone marrow-derived mesenchymal stem cells (BM-MSCs) transplanted into acellular nerve grafts (ANGs) could repair nerve defects compared with nerve isografts and ANGs with BM-MSCs. METHODS: BM-MSCs extracted, separated and purified from the bone marrow of rats, and some of the BM-MSCs were cultured with mixed induction agents that could induce BM-MSCs into SLCs. Either SLCs or BM-MSCs were seeded onto 10-mm ANGs, and the isografts were chosen as the control. The walking-track test, tibialis anterior muscle weight measurement, electrophysiological examination, toluidine blue staining, transmission electron micrographs and immunostaining of S-100 and VEGF in these three groups were evaluated in a 10-mm rat sciatic injury-repair model. RESULTS: The walking-track test, tibialis anterior muscle weight measurement and electrophysiological examination of the sciatic nerve suggested the groups of ANGs with SLCs and isografts obtained better results than the BM-MSC group (P < 0.05). Meanwhile, the results of the SLCs and isograft groups were similar (P > 0.05). All the histomorphometric analyses (toluidine blue staining, transmission electron micrographs and immunostaining of S-100 and VEGF) showed that there were more regenerating nerve fibers in the group of ANGs with SLCs than the BM-MSCs (P < 0.05), but there was no significant difference between the SLC and isograft groups (P > 0.05). CONCLUSIONS: SLCs seeded in ANGs and isografts show better functional regeneration compared with BM-MSCs seeded in ANGs. Additionally, SLCs combined with ANGs present almost the same outcome as the isografts. Therefore, SLCs with ANGs can be a good choice in nerve defect repairs.